STIGMA MASYARAKAT TERHADAP PENDERITA GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS LIMBOTO BARAT - Firmawati Firmawati; Rona Febriyona; Renalda Rengkung (Jurnal Anestesi, 2023)
People with mental disorders often experience a greater stigma than the surrounding community, stigma will further worsen the condition of mental patients, for example, sufferers find it difficult to interact socially with society and even cause suicide. The purpose of this study was to determine the stigma of the community towards people with mental disorders in the West Limboto Health Center Work Area. The research design used qualitative with a phenomenological study approach, the research participants were people in the West Limboto Puskesmas Working Area with 6 people who met the sample criteria and 1 health worker as the person in charge of the psychiatric section at the Puskesmas. The findings obtained there is a stigma of society in the form of stereotypes of the causes of mental disorders (stress, disappointment and desires that are not achieved) and people with mental disorders are considered dangerous, a form of stigma labeling, namely people with mental disorders are nicknamed lunatics to distinguish them from people around them and as someone who is dangerous, while the stigma form of discrimination, namely people with mental disorders are avoided, run, expelled and allow shackling actions. It can be concluded that community stigma in the form of streotypes, labels and discrimination still shows a bad stigma against people with mental disorders.